2006
DOI: 10.1902/jop.2006.050223
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cultured Oral Gingiva by Tissue Engineering Techniques Without Materials of Animal Origin

Abstract: The new cultured gingival substitute containing no animal-derived materials produced good cell proliferation and VEGF release. The results suggested that the substitute may provide a new tool for the treatment of gingival recession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In the last decades there have been great advances in this area, which led to its application in different medical fields, including periodontology. Some authors have been evaluating non-enzymatic methods of gingival fibroblasts isolation in vitro for the use in gingival augmentation (6,(10)(11)(12)(13)(14). Gingival fibroblast culture in different matrices has been studied and has shown promising results in soft tissues regeneration (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades there have been great advances in this area, which led to its application in different medical fields, including periodontology. Some authors have been evaluating non-enzymatic methods of gingival fibroblasts isolation in vitro for the use in gingival augmentation (6,(10)(11)(12)(13)(14). Gingival fibroblast culture in different matrices has been studied and has shown promising results in soft tissues regeneration (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…One of the prospective sources comes from marine organisms (sea urchins, fish scale and skin, jellyfish, shark skin). Many studies indicated that bird feet, frog skin, sea urchin and shark skin collagen have a molecular structure different than domestic animals [10][11][12]. Their amino acid composition, peptide constitution, glycosaminoglycan content and thermal behavior are significantly different from land animals.…”
mentioning
confidence: 99%
“…*0.01 \ p \ 0.05, **p \ 0.01; no asterisk means no significant difference (after applying for Bonferroni correction). Error bar means SD (N = 9) Cytotechnology (2015) 67:507-514 511 to Eagle's minimal essential medium: HEPES, L-glutamine, lipids, sodium bicarbonate, sodium selenite, gentamicin sulfate, non-essential amino acids, recombinant human insulin, recombinant human epidermal growth factor, dexamethasone, and synthetic polymer (Itoh and Hoshi 2005;Yamada et al 2006;Morimoto et al 2011;Takami et al 2008). It contains no animal-derived components and is thought to promote a normal fibroblast phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Dulbecco's modified Eagle medium (DMEM) plus fetal bovine serum (FBS) is usually used for human fibroblast culture (Rittié and Fisher 2005). An autologous serum can be used in place of FBS (Itoh and Hoshi 2005;Yamada et al 2006;Nishi et al 2010;Morimoto et al 2011). Fibroblasts cultured with serum have a high proliferative capacity, similar to that of keloids; however, human fibroblasts in living dermis rarely proliferate and maintain homeostasis of the dermis through collagen production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation